Tribes in Transition: Socioeconomic Challenges in Urban Slums and Resettlement Zones - Mondal, Debdas (Unisia, 2025)
Urbanization in India has led to significant migration of tribal populations into urban slums, peripheral areas, and resettlement zones. This study examines the socioeconomic conditions, health status, cultural transitions, and policy impacts on tribal communities in these settings. Utilizing data from government reports, academic studies, and field surveys, the research highlights the challenges faced by tribal populations and the effectiveness of resettlement policies. This study explores the socioeconomic challenges faced by tribal communities undergoing urban transition, particularly those residing in slums and government-designated resettlement zones. As tribal populations migrate or are displaced from traditional habitats to urban peripheries, they encounter a complex web of marginalization, cultural disintegration, economic instability, and inadequate access to basic services. The paper examines how forced urbanization and relocation disrupt indigenous ways of life, affecting livelihood patterns, education, health, and social cohesion. Drawing from field studies, government reports, and academic literature, it highlights the gaps in policy implementation and the resilience strategies adopted by these communities. The analysis also emphasizes the need for culturally sensitive urban planning and inclusive development policies that acknowledge tribal identities while facilitating equitable integration into the urban fabric. By illuminating the lived experiences of tribal groups in transition, the study aims to contribute to a more nuanced understanding of urban poverty and displacement in contemporary India.